2021
DOI: 10.48550/arxiv.2111.10904
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Policy Learning Under Ambiguity

Abstract: This paper studies the problem of estimating individualized treatment rules when treatment effects are partially identified, as it is often the case with observational data. We first study the population problem of assigning treatment under partial identification and derive the population optimal policies using classic optimality criteria for decision under ambiguity. We then propose an algorithm for computation of the estimated optimal treatment policy and provide statistical guarantees for its convergence to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The Japanese Economic Review (2023) 74:573-602 on partially identified welfare, including issues like distributional robustness, external validity or asymmetric welfare, by, e.g., Adjaho and Christensen (2022), Ben-Michael et al (2021, 2022, Christensen et al (2023), D'Adamo (2021, Ishihara and Kitagawa (2021), Kallus and Zhou (2018), Kido (2022), Lei et al (2023). When welfare is pointidentified, finite-sample optimal rules are derived in Porter (2009, 2020), Schlag (2006), Stoye (2009a), andTetenov (2012b).…”
mentioning
confidence: 99%
“…The Japanese Economic Review (2023) 74:573-602 on partially identified welfare, including issues like distributional robustness, external validity or asymmetric welfare, by, e.g., Adjaho and Christensen (2022), Ben-Michael et al (2021, 2022, Christensen et al (2023), D'Adamo (2021, Ishihara and Kitagawa (2021), Kallus and Zhou (2018), Kido (2022), Lei et al (2023). When welfare is pointidentified, finite-sample optimal rules are derived in Porter (2009, 2020), Schlag (2006), Stoye (2009a), andTetenov (2012b).…”
mentioning
confidence: 99%